Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

solve the following quadratic equation by extracting the square root.
4(m-1)²-4=0
thank u!!!


Sagot :

Step-by-step explanation:

[tex] \sqrt{} 4(m - 1) ^{2} = \sqrt{} 4 [/tex]

Answer:

4(m-1)^2=4

(2(m-1))^2=2^2

2(m-1)=2

2m-2=2

2m=4

m=2